China's Bond Market and Global Financial Markets - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2018)
A cross-country comparative analysis shows that there is substantial room for further integration of China into global financial markets, especially in the case of the international bond market. A further successful liberalization of the Chinese bond market would encompass not only loosening bond market regulations, but also further developing of other markets, notably the foreign exchange market. Even though the increased integration of China into international capital markets would increase its exposure to the global financial cycle, the costs in terms of monetary autonomy would not be large given China's size and especially under a well-articulated macroeconomic framework.